1994
DOI: 10.1002/recl.19941131011
|View full text |Cite
|
Sign up to set email alerts
|

A model for the enantioselective hydrogenation of pyruvate catalysed by alkaloid‐modified platinum

Abstract: Red. Trav. Chim. Pays-Bas 113, 465-474 (1994) SSDl 0 1 6 5 -0 5 1 3 ( 9 4 ) 0 0 0 3 8 -4 Abstract.A LEED and XPS study of the adsorption of naphthalene, quinoline, and 10,11-dihydrocinchonidine on Pt(ll1) at 300K has shown that only naphthalene forms an ordered ad-layer, and that quinoline and the alkaloid adsorb in a disordered state and without decomposition. These experiments do not support the hypothesis of ordered adsorption of alkaloid that forms the basis of the template model for the interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
110
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 35 publications
6
110
0
Order By: Relevance
“…To find a feasible explanation we have to consider the possible adsorption modes of substrate and modifier on the metal surface and their interaction during hydrogen uptake. According to the mechanistic models, developed for the hydrogenation of 1 over Pt by Wells et al [35] and our group, [31,36] the cinchona alkaloid adsorbs via the quinoline rings lying parallel to the Pt surface (p-bonded ™anchoring moiety∫). The substrate 1 adsorbs also flat via the C O bonds parallel to the Pt surface (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To find a feasible explanation we have to consider the possible adsorption modes of substrate and modifier on the metal surface and their interaction during hydrogen uptake. According to the mechanistic models, developed for the hydrogenation of 1 over Pt by Wells et al [35] and our group, [31,36] the cinchona alkaloid adsorbs via the quinoline rings lying parallel to the Pt surface (p-bonded ™anchoring moiety∫). The substrate 1 adsorbs also flat via the C O bonds parallel to the Pt surface (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…In AcOH this interaction corresponds to the 1-protonated CD interaction, [37] in apolar medium the complex resembles the half-hydrogenated state of 1. [35] At least three differently adsorbed species could be identified by in situ ATR-studies of CD adsorption on platinum:…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that, using cinchonidine chiral alkaloid, it is possible to induce a preferential formation of (R)-lactate. [43][44] In the present study the enantioselective hydrogenation of ethyl pyruvate was carried out in liquid phase at 298 K and 40 bar overall pressure on colloidal platinum and on Pt-CD/SiO 2 catalysts obtained by impregnation of the colloids on the support. Experimental variables such as the weight of the catalysts and the concentration of CD added with the substrate during the reaction were also studied.…”
Section: Resultsmentioning
confidence: 99%
“…The approach has the inherent advantage that the results are related to truly in situ conditions. This strategy has been applied extensively for the hydrogenation of pyruvate esters on Pt, including some cinchona alkaloid derivatives, [21 -26] other alkaloids, [27 -30] various amines, [31,32] amino alcohols, [33 -37] amino acids, [38] and amino acid derivatives. [39,40] The most important conclusions emerging from these studies are that CD and many other effective modifiers adsorb via the extended aromatic ring lying close to parallel to the Pt surface, and the basic N-atom is responsible for interacting with the substrate in the enantiodifferentiating step.…”
Section: Introductionmentioning
confidence: 99%